2018
DOI: 10.1007/s11051-018-4181-y
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized TiO2 nanoparticles labelled with 225Ac for targeted alpha radionuclide therapy

Abstract: The 225Ac radioisotope exhibits very attractive nuclear properties for application in radionuclide therapy. Unfortunately, the major challenge for radioconjugates labelled with 225Ac is that traditional chelating moieties are unable to sequester the radioactive daughters in the bioconjugate which is critical to minimize toxicity to healthy, non-targeted tissues. In the present work, we propose to apply TiO2 nanoparticles (NPs) as carrier for 225Ac and its decay products. The surface of TiO2 nanoparticles with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…In human serum, the fraction of 225 Ac released from 225 Ac@Fe3O4 was still less than 2%, but the retention of 221 Fr and 213 Bi decreased to 70% after 10 days. Our results are comparable or slightly better, especially in the case of released daughter radionuclides, as observed previously on 225 Ac-labeled titanium oxide [40] nanoparticles and Fe3O4 NPs labeled with 223 Ra [28]. The obtained results can be interpreted on the basis of recoil energy in the 225 Ac → 221 Fr decay reaction and subsequent α decays [41].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In human serum, the fraction of 225 Ac released from 225 Ac@Fe3O4 was still less than 2%, but the retention of 221 Fr and 213 Bi decreased to 70% after 10 days. Our results are comparable or slightly better, especially in the case of released daughter radionuclides, as observed previously on 225 Ac-labeled titanium oxide [40] nanoparticles and Fe3O4 NPs labeled with 223 Ra [28]. The obtained results can be interpreted on the basis of recoil energy in the 225 Ac → 221 Fr decay reaction and subsequent α decays [41].…”
Section: Resultssupporting
confidence: 89%
“…Synthesized nanoparticles were tested for the determination of leaching of the mother radionuclide 225 Ac and its decay daughters as described earlier [40]. Briefly, a portion of radiolabeled nanoparticles was placed in a dialysis tube (D-Tube Dializer Midi with 3.5 kDa cut-off membrane, Novagen) and was dialyzed against 20 mL of 0.9% NaCl or 1 mM PBS for up to 10 days at room temperature.…”
Section: Stability Studies Of 225 Ac@fe 3 O 4 Nanoparticlesmentioning
confidence: 99%
“…During the past decade, an increasing number of studies have been reported on tumor treatment with radiolabeled NPs, most of which have been performed with NPs radiolabeled with the β-emitting isotope Lutetium-177 ( 177 Lu, half-life: t 1/2 = 6.7 d) [12,[19][20][21][22][23][24]. Regarding 225 Ac, only a few studies have examined NPs radiolabeled with this radionuclide for tumor treatment [25][26][27]. The present work was designed to investigate a gold nanoparticle radiolabeled with an α-emitter as an injectable radiopharmaceutical form of BRT for local radiation treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies dedicated to labelling of TiO 2 with 48 V or 125 I for in vivo toxicological studies 22,23 and with 225 Ac for targeted alpha radionuclide therapy. 24 This article is focused on the study of 223 Ra sorption on nHAp and nTiO 2 . The published data on radium sorption using chosen nanoparticles are quite limited and available papers are focused mainly on 226 Ra behavior in uranium mill tailings and the articles studied only iron compounds as a goethite or ferrihydrite, or environmental minerals.…”
Section: Introductionmentioning
confidence: 99%